Impact of Spin State Transition on Vibrations of [Fe–(PM–BiA)2(NCS)2] and [Fe–(PM–PEA)2(NCS)2] Spin Crossover Compounds: Experimental and Theoretical Far IR and Raman Study. Issue 3 (17th January 2018) - Ould‐Hamouda, Amine; Viquerat, Benjamin; Degert, Jérôme; Matar, Samir F.; Létard, Jean François; Guillaume, François; Freysz, Eric
Abstract : Far IR and Raman spectroscopy of [Fe–(PM–BiA)2 (NCS)2 ] and [Fe–(PM–PEA)2 (NCS)2 ] were performed to record the vibration modes of these complexes and their evolutions during spin state transition. THz spectroscopy was used to measure the far IR absorption of these compounds down to 20 cm –1 . Using density functional theory calculations, we were able to retrieve and to visualize these vibrations in both high‐spin and low‐spin states. In both compounds, Raman spectra recorded in the 800–2250 cm –1 wavenumber range are well accounted for by our computations. For far IR vibration modes, most of the experimental absorption peaks above 100 cm –1 are well reproduced. However, below 100 cm –1, marked differences were recorded. For [Fe–(PM–BiA)2 (NCS)2 ], we demonstrate that the interactions with surrounding molecules impact the computed far IR spectra non‐negligibly and can partly correct this difference. Abstract : We report on the Raman and terahertz (THz) spectroscopy of [Fe–(PM–BiA)2 (NCS)2 ] and [Fe–(PM–PEA)2 (NCS)2 ] spin crossover compounds in the high‐spin and low‐spin states. These are compared to spectra computed using density functional theory. While the computed and experimental data agree, we demonstrate that the interaction with surrounding molecules impacts the computed THz spectra non‐negligibly.